2018
DOI: 10.1038/nm.4456
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent ECSIT mutation encoding V140A triggers hyperinflammation and promotes hemophagocytic syndrome in extranodal NK/T cell lymphoma

Abstract: Hemophagocytic syndrome (HPS) is a fatal hyperinflammatory disease with a poorly understood mechanism that occurs most frequently in extranodal natural killer/T cell lymphoma (ENKTL). Through exome sequencing of ENKTL tumor-normal samples, we have identified a hotspot mutation (c.419T>C) in the evolutionarily conserved signaling intermediate in Toll pathway (ECSIT) gene, encoding a V140A variant of ECSIT. ECSIT-V140A activated NF-κB more potently than the wild-type protein owing to its increased affinity for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 48 publications
0
56
0
Order By: Relevance
“…In addition, previous work suggests that lenalidomide, a derivative of thalidomide, can restore T cells motility leading to their activation 26 . Finally, it was also reported that thalidomide prevents NF-kB from binding to the promoters of its target genes, including TNF-alpha and IFN-Gamma thereby reducing excessive inflammatory response 27,28 . Altogether, based on these previous studies, the reported successful use of thalidomide by Chen et al 24 , and our analysis, we hypothesize that thalidomide can be effective against COVID-2019 by modifying favourably immune response of the infected patients against the virus ( Figure 5).…”
Section: Results Sharing and Case Analysismentioning
confidence: 99%
“…In addition, previous work suggests that lenalidomide, a derivative of thalidomide, can restore T cells motility leading to their activation 26 . Finally, it was also reported that thalidomide prevents NF-kB from binding to the promoters of its target genes, including TNF-alpha and IFN-Gamma thereby reducing excessive inflammatory response 27,28 . Altogether, based on these previous studies, the reported successful use of thalidomide by Chen et al 24 , and our analysis, we hypothesize that thalidomide can be effective against COVID-2019 by modifying favourably immune response of the infected patients against the virus ( Figure 5).…”
Section: Results Sharing and Case Analysismentioning
confidence: 99%
“…The function of the MCIA complex is supported by the existence of CI deficiency in patients harboring mutations in genes encoding components of this complex ( Alston et al, 2016 ; Fassone et al, 2011 ; Mimaki et al, 2012 ; Nouws et al, 2010 ). So far, only one ECSIT mutation has been identified in human disease, the V140A variant that triggers hyperinflammation and promotes hyperphagocytic syndrome in extranodal natural killer/T cell lymphoma (ENKTL) ( Wen et al, 2018 ). Furthermore, ECSIT function has only been examined using downregulation in cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…It was of peculiar interest to us that the two GNAQ hotspot somatic mutations (p.T96S and p.Y101X) reported in this study were never reported in other NKTCL studies that used NGS too [3][4][5][6] . We analyzed the Sanger sequences provided in Supplementary Fig.…”
Section: Recurrent Pt96s and Py101x Somatic Mutations Are Potentialmentioning
confidence: 59%